2009
DOI: 10.1038/hr.2009.87
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of hypertension for the development of tailored medicine

Abstract: Similar to a tsunami wave, a new surge of genome-wide association studies in common complex diseases has succeeded in identifying the causative genetic risk factors of hypertension. The current status of genomic studies in hypertension, however, remains disorganized, and there are no clear solutions in sight. One possible reason for this disorganization is the small effect of each genetic variant on the predisposition to hypertension. Another reason could be that the morbidity of hypertension is typically used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…2 Thus, over the last decade, many genetic studies have aimed to clarify the causal genes of hypertension, as reviewed previously. 3 Genetic research on hypertension started using the candidate gene approach by investigating renin-angiotensin system (RAS)-related genes. [4][5][6] Recently, several large-scale genome-wide association studies (GWASs) for hypertension [7][8][9] were performed, and B50 single nucleotide polymorphisms (SNPs) were identified as possible causal genes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thus, over the last decade, many genetic studies have aimed to clarify the causal genes of hypertension, as reviewed previously. 3 Genetic research on hypertension started using the candidate gene approach by investigating renin-angiotensin system (RAS)-related genes. [4][5][6] Recently, several large-scale genome-wide association studies (GWASs) for hypertension [7][8][9] were performed, and B50 single nucleotide polymorphisms (SNPs) were identified as possible causal genes.…”
Section: Introductionmentioning
confidence: 99%
“…Hunt and associates suggested that preventatively reducing salt is the ideal intervention for people with high salt sensitivity. Therefore, salt reduction is likely the most effective approach for the prevention of hypertension in Japanese persons who are genetically sensitive to dietary salt …”
mentioning
confidence: 99%